Analysis of The Contribution of Driver's License Revenue and Police Record Certificate to Non-Tax State Revenue - Isnayni, Nadila; Herman , H.; Frida Suryati, Tri (Golden Ratio of Social Science and Education, 2024)
This study aims, first, to determine the management of non-tax state revenue (PNBP) of driving license (SIM) at Mamuju Police Station, second, to determine the management of non-tax state revenue (PNBP) of police record certificate (SKCK) at Mamuju Police Station and third, to determine the contribution of PNBP SIM and SKCK to total PNBP at Mamuju Police Station. The research method used is descriptive method, namely the secondary data obtained is described. The research results that the issuance of SIM and SKCK is based on the SOP issued by the Chief of Police of Mamuju. The contribution of SIM to PNBP is above 65% while the contribution of SKCK is below 20% in the 2019-2023 period.